Association between estimated glucose disposal rate and major adverse cardiovascular events in patients with type 2 diabetes. - Maojun Liu; Junyu Pei; Xinqun Hu; Xiaopu Wang (PLoS ONE)
Background Estimated glucose disposal rate (eGDR) is associated with risk of adverse outcomes in patients with type 2 diabetes. However, whether eGDR affects long-term glycemic management in patients with type 2 diabetes remains unclear. This study aimed to investigate the relationships between eGDR, long-term visit-to-visit HbA1c variability, and adverse outcomes in patients with type 2 diabetes. Methods This post-hoc analysis of the Action to Control Cardiovascular Risk in Diabetes study (ACCORD) included 10,129 type 2 diabetes patients with high cardiovascular risk. Participants were divided into tertiles based on eGDR values. HbA1c variability was assessed using the HbA1c Variability Score (HVS). Primary outcome was major adverse cardiovascular events (MACEs), composite of nonfatal myocardial infarction, nonfatal stroke, and death from cardiovascular causes. Weibull accelerated failure-time models and causal mediation analyses were employed to evaluate relationships between variables. Results During a median follow-up of 4.75 years, compared to T1, T3 showed significantly higher risks of MACEs (HR 1.56, 95% CI: 1.27-1.91) and all-cause mortality (HR 1.81, 95% CI: 1.40-2.32) in fully adjusted models. Restricted cubic spline analysis revealed nonlinear relationships between eGDR and outcomes, with risk declining rapidly as eGDR increased until approximately 5 mg/kg/min, after which the curve flattened. A significant negative correlation was observed between HVS and eGDR (β -2.30; 95% CI: -2.65 to -1.95), following a similar nonlinear pattern. In mediation analysis, HVS explained 37.8% of eGDR's effect on MACEs risk and 21.53% of its effect on all-cause mortality. Conclusion In type 2 diabetes patients with high cardiovascular risk, lower eGDR was associated with higher risk of MACEs and all-cause mortality, with HbA1c variability playing an important mediating role in this relationship.